Optimal Entry Point for French Immersion - Netten, Joan (Revue de l'Université de Moncton)

(untitled) (Revue de l'Université de Moncton, 2007)
Abstract This discussion will be divided into three sections. In the first, I wish to present for your consideration certain general principles of bilingual education which need to be taken into account in making decisions about entry into immersion programs. Secondly, we will examine the three major forms of immersion education, early, middle and late, to determine the advantages and disadvantages of each, and lastly, I will share with you my perceptions as to which point might be considered an optimal one for entry into French immersion.